EVALUASI KUALITAS LAYANAN STAF BOARDING GATE CITILINK DI YOGYAKARTA INTERNATIONAL AIRPORT - Fadillah, Ratu; Hidayatullah, Hidayatullah (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This study analyzes the quality level of service provided by Citilink's boarding gate staff at Yogyakarta International Airport (YIA) in executing boarding procedures according to Standard Operating Procedures (SOP). The research results show that Citilink's boarding gate staff at YIA are able to organize and manage the boarding procedures quickly and efficiently, allowing passengers to board the aircraft on time without any hindrance. The staff's compliance with the established SOPs is a major factor supporting passenger satisfaction. In addition to compliance with SOPs, other supporting factors in improving service quality include the availability of additional facilities that facilitate the staff's performance. However, this study also identifies several inhibiting factors, such as operational aircraft issues that cause delays and passenger dissatisfaction with staff services. To address these obstacles, this study proposes several solutions. First, providing compensation to passengers in the event of a delay as a form of responsibility and fairness. Second, the staff should continuously improve service quality to meet passenger satisfaction. Third, enhancing communication between boarding gate staff and passengers to provide clear and accurate information regarding the boarding process.